(untitled) (Simbiótica. Revista Eletrônica, 2023)
The purpose of this article is to discuss the phenomenon of the “psychologization of society” and demonstrate how the democratization of the language of psi sciences contributed to the modern perspective of the self. Thus, I argue that this view legitimizes a figure of an interiorized, solitary and irreducible subject, a thinking “I”, in which health and illness belong and are confined especially within oneself. In addition, I discuss how hegemonic self-help literature, behavioral therapies, psychiatry and neuroscience seek and offer self-control and management, connecting to the neoliberal management of psychic suffering in the context of financial capitalism.